A window to the outside: The Reading Group as defense, meeting and resistance - Maria Elena Scotti; Jole Orsenigo (University of Bologna, 2022)
This paper presents qualitative research that focus on the Reading Groups. The aim is to understand the values of reading and discussing books in group, during the months of lockdown, caused by the Covid-19 health emergency. Using written and structured interviews, we collected the experiences of 73 adult participants in Reading Group in Milan and Bergamo provinces. The results show how, even by the unusual online mode, the Reading Group was a way to defend oneself from the pain of reality, a space of relationship in isolation and a possibility of self-assertion, in situation of strong limitation of individual freedom. Starting from the analysis of what happened, this study wants to outline the potential of Reading Groups as pedagogical environments to produce change.